Effect Chemical and Physical Properties of Tigris River Water on Low Carbon Steel Corrosion in Wasit Governorate - Sadik Hameed; Hussein Ali Awad AL-Zamili; Blqees Raheem Odhafa; Raheem A. H. Al-Uqaily; Subhi A.H. Al-Bayaty (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study focused at how the resistance of carbon iron to electrochemical corrosion was effected by the chemical and physical characteristics of the Tigris River water at different locations of Wasit City. For each of these four locations, models were obtained. Al-Ahrar, Al-Kut, Al-Zubaidiyah, and Al-Numaniyah. Models were obtained for four of these locations Al-Zubaidiyah, Al-Numaniyah, Al-Ahrar, and Al-Kutand their chemical qualities were estimated and determined. The results of the cathodic and anodic behavior are represented by two curves. Two tangents have been drawn for these two curves, and their point of capture indicates the value of the current that causes corrosion and the corrosion voltage.According to the findings the most corrosion occurred in the Al-Kut area due to the combination of high percentage of chlorides than other locations and a high concentration of dissolved oxygen, which causes rust when iron and oxygen come together.